Teledentistry's evolution post-COVID-19 : moving from crisis response to long-term solutions = La evolución de la teledetección después del COVID-19 : el paso de la respuesta a la crisis a las soluciones a largo plazo - Mohamed Kamel, Amany Hany
Telehealth, the use of telecommunications technology and electronic information to aid in healthcare delivery, has revolutionized patient care. Health communities have already approved telemedicine for treating certain acute and chronic diseases, while teledentistry has emerged as a distinct field within the broader scope of telemedicine. Numerous trials have demonstrated the value of teledentistry in reducing dental expenses and expanding dental care access to remote and rural areas. With technological advancements, teledentistry holds the potential to further enhance dental services and patient care. The COVID-19 pandemic has brought healthcare to the forefront of public concern. The need for close face-to-face contact with patients largely led to the suspension of dentistry services. However, the increased use of cell phones and related software packages integrated into "teledentistry" has facilitated easier clinical data exchange between patients and clinicians. This technology proved invaluable for dentists managing dental emergencies during lockdowns, providing an innovative means to resume dental practice. As a result, integrating teledentistry into routine dental practice as a complement to the existing dental system is advisable. It has the potential to revolutionize dental care for the better by expanding access to care and decreasing expenses. Given these circumstances, this review discusses the value and implications of teledentistry, highlighting its potential as a game-changing solution for the dental industry.